2013
DOI: 10.1186/1687-6180-2013-154
|View full text |Cite
|
Sign up to set email alerts
|

Novel solutions for side information generation and fusion in multiview DVC

Abstract: One of the key problems in distributed video coding is the generation of side information. This task consists of producing an estimate of an image with some neighboring ones, such as those taken by the same camera at different time instants, or, in the case of multiview setups, images taken at the same time instant by different cameras. If both estimates are available, a further problem arises, which is how to merge them in order to create a single side information. This problem is very relevant since a good e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Motion and disparity compensated difference linear fusion (MDCD-Lin) is a multiview fusion technique [8] used as benchmark in [9,12]. The techniques presented in [9] are shown to perform either as well as MDCD-Lin or as well as the best single SI decoder.…”
Section: Benchmarks For Si Fusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Motion and disparity compensated difference linear fusion (MDCD-Lin) is a multiview fusion technique [8] used as benchmark in [9,12]. The techniques presented in [9] are shown to perform either as well as MDCD-Lin or as well as the best single SI decoder.…”
Section: Benchmarks For Si Fusionmentioning
confidence: 99%
“…MVME demonstrates high performance in fast-motion sequences, but it is outperformed by motion compensation and interpolation techniques in slowmotion cases [11]. More recently [12], a modified version of the temporal motion estimation algorithm employed in DISCOVER [13] is proposed for inter-view SI generation. The key novelty is the penalization of small disparities, which characterizes background blocks.…”
Section: Inter-view Si Creationmentioning
confidence: 99%
See 2 more Smart Citations
“…The review of several important side information generation methods can be found in [8]. Additionally, new applications of DVC in [9,10] are inspired with these investigations.…”
Section: Introductionmentioning
confidence: 99%